Factors associated with digital piracy among early adolescents. (February 2018) - Lee, Byung; Paek, Seung Yeop; Fenoff, Roy
Abstract: With increasing capacity for storing and transmitting digital content via peer-to-peer networks, digital piracy remains to be a growing concern for various industries worldwide. Concurrently, young people have been at the forefront of adopting and using new technology to share or distribute information with one another. Given that the majority of existing studies have relied on college samples, it is valuable to explore the factors associated with digital piracy among adolescents in non-Western cultures. Using a South Korean sample and multivariate logistic regression, the current study found that association with deviant peers as well as attitudinal and perception indicators are linked with one's participation in digital piracy. These findings suggest that in addition to peer association, an individual's moral attitude toward and perceived legality of digital piracy play a role in the illegal downloading and unauthorized uploading of copyrighted media files among youth. Implications for research and policy are discussed. Highlights: Associating with deviant peers on-line is positively related to participation in digital piracy. A person's moral attitude toward the act of downloading via file-sharing programs is linked with participation in digital piracy. Perceived legality can influence participation in digital piracy. Daily time spent on-line using entertainment media is positively related to participation in digital piracy.